Hubungan pH, Hidrasi, Kapasitas Bufer Saliva, Jumlah Streptococcus Mutans dengan Keparahan Karies pada Anak Rampan Karies - Ani Subekti; Nany Kristiani; Hermin Rimbyastuti (Jurnal Riset Kesehatan, 2013)
Rampan caries is the habit of bottle feeding at night, sweets preference and often meals sucking. Saliva is one of the factors that may influence the occurrence of caries. Some of the factors that cause caries saliva such as saliva pH, hydration, microorganisms of the oral cavity and salivary buffer capacity.The research objective was to determine the relationship of hydration, pH, buffer capacity salivary and growth Streptoccoccus mutans against caries severity or deft.A sample of 30 kindergartens ABA Banyumanik Semarang with rampan caries criteria. Age samples between 4-6 years. Examination of caries severity measured by deft. Measurement of hydration with methods the water droplets on the surface of the labial mucosa of the lower lip. Measuring pH with pHmeter. A buffer capacity of saliva measured by acid-base titration. Measured Streptoccoccus mutans growth with agar culture method.The results showed the average of caries index (deft)  in children kindergarten ABA Banyumanik Semarang was 7.167. While hydration saliva was 12.867, while the pH of saliva average was 6.517 and the number of Streptococcus mutans on average 6.7 x 102 CFU / ml. Multiple linear regression statistical tests showed that there was a significant relationship between the simultaneous hydration, pH, buffer capacity of saliva, the growth of Streptococcus mutans with caries severity (deft). Partial correlation test of the four independent variables showed only hydration showed no relationship with deft. While pH, buffer capacity, and the number of Streptococcus mutans demonstrated relationship to deft.